An Appraisal Analysis Of Narrative Text From The 11th Grade English Textbook - Magfiroh, Iroh; Herdiawan, Rama Dwika; Rofi'i, Agus (Allure Journal, 2021)
This present study explain the appraisal devices especially the attitude types. Appraisal theory is the development of Systemic Functional Linguistics theory in the realm of interpersonal meaning initiated by Martin and White. This study used qualitative research with discourse analysis (DA) techniques. The object of analysis in this study is narrative text of the English textbooks for senior high school students published by the Ministry of Education and Culture. This study employed a document analysis as a technique for collecting data. The findings showed that there were 65 systems of attitude which consist of 19 positive affect, 25 negative affect, 8 positive judgment, 8 negative judgment, 1 positive appreciation, and 4 negative appreciation.